Harumanis Mango: Perspectives in Disease Management and Advancement using Interdigitated Electrodes (IDE) Nano-Biosensor. Issue 1 (May 2020) - Uda, M N A; Gopinath, Subash C B; Hashim, U; Hakimi, Asyraf; Afnan Uda, M N; Anuar, Aminudin; Bakar, M A A; Sulaiman, M K; Parmin, N A
Abstract: The agriculture sector plays an important role in economic development in providing rural employment, uplifting rural incomes and ensuring national food security. Harumanis mango has been predominantly produced in the Perlis state of Malaysia, and it is the seasonal once-a-year. However, plant diseases became a serious issue that significantly affects both the quality and quantity of Harumanis mango production. The primary problem with Harumanis mango has experienced by farmers is a disease and the farmers are failed to complete the process of post-harvest for Harumanis mango. Further, in the case of Harumanis mango disease, the symptoms are often detected at the later stage, which makes it difficult to take any further action. Usually, the diseases are controlled by fungicides and the use of synthetic chemicals to eliminate the postharvest diseases and deterioration has their limit due to carcinogenicity, teratogenicity, environmental pollution, effects on food and other side-effects on humans. Up to date, the control of Harumanis mango disease is still challenging, although several studies have been conducted to eradicate and prevent its outbreak in the field. This overview is about Harumanis mango and the prospect in preventing a serious outbreak with Harumanis mango production using interdigitated electrodes (IDE) nano-biosensor.